Gambaran Burnout Akademik Mahasiswa Kedokteran Universitas Airlangga Angkatan 2021 - Qurrota A'yunin; Widati Fatmaningrum; Soetjipto Soetjipto (Universitas Batanghari Jambi, 2023)
A heavy academic burden puts medical students at a higher risk of experiencing academic burnout when compared to the general population. Academic burnout is a term used to describe emotional reactions in the form of fatigue, depersonalization, and decreased self-efficacy in students. This study aims to determine the description of academic burnout in Airlangga University medical students class of 2021. This study used an observational analytic study design with a cross-sectional research design to determine the description of academic burnout in medical study program students. This research was conducted at the Faculty of Medicine, Airlangga University in February–May 2023. Measurement of the level of academic burnout in students was carried out using an online school burnout inventory questionnaire via gform. Respondents who took part in the study amounted to 93 respondents with the majority of respondents 60 students (64.5%) were female and 33 students (35.5%) were male, the age of the respondents was 17-21 years. The most common category of academic burnout found in low category of academic burnout represented by 30 students (32.3%), 8 students (8.6%) with very low academic burnout, 28 students (30.1%) with medium academic burnout, 22 students (23.7%) with high academic burnout, and 5 students (5.4%) with very high academic burnout.